“Evaluación de herbicidas sistémicos en el control de malezas cyperáceas en el cultivo de arroz (Oryza sativa L.), en condiciones de secano”. - Camino Mayorga, Isamara Abigail (2018)
VIII. SUMMARY The present experimental work was established in the lands of the CEDEGE Irrigation Project "Cedral II" owned by Mr. René Arnulfo Camino Morejón, located at km. 12 of the Babahoyo-Montalvo road, enter the geographic coordinates of 277438.27 UTM of west longitude and 110597.97 UTM of south latitude, the farm is located at a height of 8m.s.n.m. The zone presents a humid tropical climate, with an average annual temperature of 25.60 ° C; an annual rainfall of 2 298.8 mm, humidity 82% and 998.2 hours of annual average heliophany. The soil has a flat topography, a loamy clay texture and regular drainage. Rice seed INIAP 14, developed by the National Autonomous Institute of Agricultural Research (INIAP), was used as a study material. The treatments consisted of herbicides in different doses such as Pyrazosulfuron ethyl 10 Wp in doses of 200, 300 and 400 g / ha; Bispyribac sodium 400 in doses of 200, 300 and 400 g / ha; Pyrazosulfuron ethyl 10 Wp + Bispyribac sodium 400 in doses of 200 g + 200 cc, 200 g + 300 cc, 200 g + 400 cc and Bentazon in a dose of 300 cc / ha in Post-emergence. The experimental design of Complete Blocks at Random was used, with ten treatments and three repetitions. The evaluated variables were subjected to random block analysis and separation of means, using the Tukey significance test at 95% probability. All the necessary agricultural work was carried out in the cultivation of rice for its normal development, such as soil analysis, land preparation, sowing, irrigation, fertilization, weed control, phytosanitary control and harvesting. To estimate the effects of the treatments, the toxicity index data were taken in the crop at 7, 14 days after the application of the herbicides, Weed control at 14 and 21 days after the application of the herbicides in each treatment, height of plant, number of tillers, number of panicles, length of the panicles, grains per panicle, weight of 1000 grains, yield and economic analysis. Based on the results obtained, it was determined that the evaluation of systemic herbicides in the control of cyperaceous weeds in rice cultivation showed favorable effects; the application of Pyrazosulfuron ethyl 10 Wp in doses of 300 g / ha recorded better toxicity index and control of weeds in rice cultivation; plant height stood out with the use of Pyrazosulfuron ethyl 10 Wp + Grammya 400 in doses of 200 g + 300 cc; the largest number of tillers / m2 and length of panicles was observed in the mixture of Pyrazosulfuron ethyl 10 Wp + Bispyribac sodium 400 with doses of 200 g + 200 cc, while a greater number of panicles / m2 and grains per panicles was obtained. the use of Bispyribac sodium 400 in doses of 400 cc / ha and the weight of 1000 grains and yield reached higher averages with the application of Pyrazosulfuron ethyl 10 Wp in doses of 300 g / ha. Key words: systemic herbicides, weed control, ciperáceas, rice, Pyrazosulfuron ethyl 10 Wp, Bispyribac sodium 400, Bentazon.